Balanced Nutrition Counseling Media on Knowledge, Desires, and Attitudes of Adolescents at La Tansa 2 Islamic Boarding School - Yustiana, Irna; Mardhiati, Retno; Handayani, Handayani (Jurnal Ilmiah Kesehatan (JIKA), 2024)
Health promotion is not only for pregnant women and at 1000 HPK and in the toddler years, but we prepare it from the teenage years considering in the previous discussion that the number of early marriages is increasing. The aim of this study was to determine the effectiveness of balanced nutrition counseling media on the knowledge, desires, and attitudes of adolescents at the La Tansa 2 Islamic boarding school in Rangkasbitung, Lebak, Banten in 2022. The population in this study were grade 1 junior high school students at Pondok Pesantren La Tansa Mashiro 2 in the experimental group 1, experimental group 2, and experimental group 3. The method in this study was an experiment, Quasi Experimental Design, with a Tree Group Pre-Test Post-Test design for each group. The test used is the Dependent sample T-Test Wil Coxon Two samples are related and the Independent sample T-Test Kruskal Wallis test > 3 groups are not related. The results of the study showed that there was no differences in knowledge about the message of balanced nutrition among teenagers at the La Tansa 2 Islamic boarding school, which was conducted in the animated video group, video demonstration group, and conventional media group. In conclusion, all media in this research are good and can be used to increase knowledge, attitudes and desires about balanced nutrition in grade 1 junior high school students at the La Tansa 2 Rangkasbitung-Lebak-Banten Islamic Boarding School.